2020
DOI: 10.3390/cells9010178
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the IL-37-Mediated Suppression of Inflammasome Function

Abstract: Interleukin (IL)-37 is a member of the IL-1 family of cytokines. Although its broad anti-inflammatory properties are well described, the effects of IL-37 on inflammasome function remain poorly understood. Performing gene expression analyses, ASC oligomerization/speck assays and caspase-1 assays in bone marrow-derived macrophages (BMDM), and employing an in vivo endotoxemia model, we studied how IL-37 affects the expression and maturation of IL-1β and IL-18, inflammasome activation, and pyroptosis in detail. IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…Consistent with the known functions of IL-37 21,22,65,[69][70][71][72] , IL-37tg pups were nearly completely protected from the NECdriven increases in IL-1β, IL-6, TNF, and IL-17F, and from the reduction in TGF-β 1 . Contrary to expectations, IL-37 had little effect on type 1 mediators such as IL-12 and IL-23, the distribution of ILC subsets, nor on IL-10 in NEC.…”
Section: Discussionsupporting
confidence: 70%
“…Consistent with the known functions of IL-37 21,22,65,[69][70][71][72] , IL-37tg pups were nearly completely protected from the NECdriven increases in IL-1β, IL-6, TNF, and IL-17F, and from the reduction in TGF-β 1 . Contrary to expectations, IL-37 had little effect on type 1 mediators such as IL-12 and IL-23, the distribution of ILC subsets, nor on IL-10 in NEC.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, IL-37 in vivo could inhibit NLRP3 activation also be mentioned in colitis and LPS-induced disease [19,22,[35][36][37]. In recent study, Rudloff et al reported that IL-37 significantly suppress inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [38].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, IL-37 in vivo could inhibit NLRP3 activation also in colitis- and LPS-induced disease [ 19 , 22 , 35 37 ]. In a recent study, Rudloff et al reported that IL-37 significantly suppresses inflammasome activity in vivo to ameliorate inflammasome-driven diseases, which could corroborate our study results to some extent [ 38 ].…”
Section: Discussionsupporting
confidence: 91%